Factors that impact on emergency nurses’ ethical decision-making ability - Alba, Barbara (Nursing ethics, 2018)
Background:Reliance on moral principles and professional codes has given nurses direction for ethical decision-making. However, rational models do not capture the emotion and reality of human choice. Intuitive response must be considered.Research purpose:Supporting intuition as an important ethical decision-making tool for nurses, the aim of this study was to determine relationships between intuition, years of worked nursing experience, and perceived ethical decision-making ability. A secondary aim explored the relationships between rational thought to years of worked nursing experience and perceived ethical decision-making ability.Research design and context:A non-experimental, correlational research design was used. The Rational Experiential Inventory measured intuition and rational thought. The Clinical Decision Making in Nursing Scale measured perceived ethical decision-making ability. Pearson’s r was the statistical method used to analyze three primary and two secondary research questions.Participants:A sample of 182 emergency nurses was recruited electronically through the Emergency Nurses Association. Participants were self-selected.Ethical considerations:Approval to conduct this study was obtained by the Adelphi University Institutional Review Board.Findings:A relationship between intuition and perceived ethical decision-making ability (r = .252, p = .001) was a significant finding in this study.Discussion:This study is one of the first of this nature to make a connection between intuition and nurses’ ethical decision-making ability.Conclusion:This investigation contributes to a broader understanding of the different thought processes used by emergency nurses to make ethical decisions.